Dom Pedro I of Brazil and IV of Portugal epilepsy and peculiar behavior Epilepsia e comportamento peculiar de Dom Pedro I do Brasil e IV de Portugal - Marleide da Mota Gomes; Miguel Chalub (Arquivos de Neuro-Psiquiatria)
We present medical issues related to Dom Pedro de Alcântara Bragança e Bourbon (1798-1834), first Emperor of Brazil. This is made by means of narrative revision on historical facts starting from primary and secondary sources. Dom Pedro presented familiar incidence of epilepsy. His seizures were relatively benign and scattered, supposedly started at the age of 13: idiophatic epilepsy with generalized tonic-clonic seizures only or juvenile myoclonic epilepsy. He also had behavioral disorder characterized by hypersexuality, agitation and impulsiveness. It could have facilitated his opportunistic behavior necessary of daring to transgress the conservatism of the Portuguese crown, to create the constitutional monarchism in Brazil and in Portugal. Apresentamos aspectos médicos relacionadas a Dom Pedro de Alcântara Bragança e Bourbon (1798-1834), primeiro Imperador do Brasil. Isso é feito por meio de revisão narrativa sobre fatos históricos baseados em fontes primárias ou secundárias. Dom Pedro apresentou epilepsia de incidência familiar. Suas crises eram relativamente benignas e esparsas, de início provavelmente aos 13 anos: epilepsia idiopática generalizada com crises tônico-clônicas apenas ou epilepsia mioclônica juvenil. Ele também tinha transtorno do comportamento caracterizado por hipersexualidade, agitação e impulsividade. Isso pode ter facilitado seu comportamento oportunístico necessário para ousar a transgredir o conservadorismo da coroa portuguesa e criar o monarquismo constitucional no Brasil e em Portugal.